Kyai and Nyai’s Views on the Right to Ijbar in the Jombang Islamic Boarding School Community: A Legal Philosophy Perspective - Zaidatur Rofiah; Sirojul Azmin (Al-Mawaddah: Jurnal Studi Islam dan Hukum Keluarga (Ahwal Al-Syakhsiyyah), 2024)
In legal philosophy there are principles of morality, justice and human rights for each individual in regulating human ethics with in-depth reflection regarding the laws that exist in society. This means that women also need to pay attention to their role in choosing their life partner. However, the practice of ijbar rights in marriage is currently still found in the Islamic boarding madzhab community in Jombang, so the voice of the Kyai and Nyai is needed to express their opinion because they are figures who play an important role and are embraced by the Islamic boarding madzhab community. The research carried out to answer the above questions, the author used a qualitative field research method consisting of main data, namely legal philosophy and interviews with several Kyai and Islamic boarding madzhab caregivers in Jombang. While secondary data is classical jurisprudence books, journal articles and others. The results of the research are (1) according to the views of the Kyai and jiai, the right of ijbar or mujbir guardian may be carried out on girls provided that there is a benefit between the child and the parents (guardian), but it is better not to carry out ijbar. (2) In legal philosophy with the views of Kyai and Nyai regarding the right to ijbar, there is a binding relevance where the views of Kyai and Nyai, although guided by fiqh law, still provide principles of legal philosophy including the right of women to choose their partners.